2018
DOI: 10.1007/s00221-018-5239-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of vertical posture explored with unexpected mechanical perturbations: synergy indices and motor equivalence

Abstract: We explored the relations between indices of mechanical stability of vertical posture and synergy indices under unexpected perturbations. The main hypotheses predicted higher posture-stabilizing synergy indices and higher mechanical indices of center of pressure stability during perturbations perceived by subjects as less challenging. Healthy subjects stood on a force platform and held in fully extended arms a bar attached to two loads acting downward and upward. One of the loads was unexpectedly released by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Overall, these significant relations may be useful for successful task performance. This general finding goes in line with the general conceptualisation of 'synergies for action stability' already mentioned previously (Latash 2008;Park et al 2012;Yamagata et al 2018) and in populations affected by some diseases such as Parkinson's Disease (Latash and Huang 2015). Indeed, synergies are useful for goal-directed reasons, they are useful to stabilize the body for successful task performance.…”
Section: Relation Between Synergic Movements and Task Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, these significant relations may be useful for successful task performance. This general finding goes in line with the general conceptualisation of 'synergies for action stability' already mentioned previously (Latash 2008;Park et al 2012;Yamagata et al 2018) and in populations affected by some diseases such as Parkinson's Disease (Latash and Huang 2015). Indeed, synergies are useful for goal-directed reasons, they are useful to stabilize the body for successful task performance.…”
Section: Relation Between Synergic Movements and Task Performancesupporting
confidence: 87%
“…Previously, it has been suggested that postural control may not be controlled for its own sake, but for the achievement of other goals (Stoffregen et al 1999(Stoffregen et al , 2000. Latash and colleagues have invoked the idea of synergies, specifically muscle synergies serving for action stability or stability of performance variable (Park et al 2012;Latash and Huang 2015;Yamagata et al 2018). Our proposal of synergy between eye and postural variables is the same as forwarded by these investigators as our variables exhibit task-dependent negative covariation to stabilize overall performance (stable posture).…”
Section: Significant Relations Between Eye and Head Upper Back And Lo...mentioning
confidence: 83%
“…The quickest reflexes leave no time for central-executive intervention, but slower reflexes offer wider margin for goals to change reflex expression (Kurtzer, 2015). Measuring reflexes usually involves asking participants to maintain stable postures, introducing often unexpected stimulation, and measuring the size, intensity, and direction of the reflex response (Yamagata et al, 2018). Exosystem design might benefit from leaving short-latency reflexes unconstrained and using longer-latency reflexes as points of entry through which exosystems might blend into dynamic movements.…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports that as difficult the task becomes as higher is the involvement of more proximal joints for the maintenance of balance, in particular the hip [ 5 , 14 ]. In experimental settings, the difficulty of the task is usually increased by increasing the magnitude of a perturbation, by decreasing the magnitude of the supporting surface or by changing the features of the supporting surface [ 5 , 23 , 24 , 26 ]. For example, it has been reported that by moving from a stable to an unstable surface, the angular displacement of the ankle was stable across all the testing condition, with the knee and hip displacement arising when the difficulty of the task was higher [ 5 , 45 ].…”
Section: Discussionmentioning
confidence: 99%